Envelope tracking power amplifier with pre-distortion linearization for WLAN 802.11g - Feipeng Wang; Ojo, A.; Kimball, D.; Asbeck, P.; Larson, L. (2004 IEEE MTT-S International Microwave Symposium, 2004)
This paper presents a power amplifier based on envelope tracking (ET) with application to the WLAN 802.11g system. Baseband pre-distortion is implemented to improve the linearity. A high-efficiency wide-bandwidth envelope amplifier and a GaAs MESFET class AB RFPA are designed and implemented for the system. An overall system drain efficiency of 30% is obtained for an OFDM output power of 20 dBm at 2.4GHz.